Article RETRACTED due to bad practices by the authors Comparison of Maximum Voluntary Isometric Contraction of The Quadriceps Muscle After Modified Hybrid Training with NMES - Putri Putri Ayu; Damayanti Tinduh; Yudith Dian Prawitri; Soenarnatalina Melaniani (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Reduced muscle strength is caused by decreased of physical activity and inactive limb due to disease and sedentary lifestyle. Neuro-Muscular Electrical Stimulation (NMES) Russian Protocol and also hybrid training system that provide resistance from antagonist muscle contraction to agonist muscles that contract voluntarily are alternative methods for strengthening exercises to increase muscle strength. This study aimed to analyze the effect of Hybrid modification strengthening exercise and Russian NMES protocol on Quadriceps Femoris muscle strength in healthy untrained subjects. Methods: The subjects of this study were 24 untrained healthy men aged 25-45 years, divided into the Modified Hybrid Training (MHT) Group (n=12) and the Neuro-Muscular Electrical Stimulation (NMES) Group (n=12). Both groups received intervention 3 times per week for 4 weeks (12 sessions). Maximum voluntary isometric contraction (MVIC) of quadriceps muscles measured with surface EMG before and after the intervention. Results: There was significant improvement in the MVIC value of quadriceps muscle in the modified hybrid training group (dominant limb p = 0.001, non-dominant limb p = 0.001). In the NMES group, there were also significant improvement in Maximum Voluntary Isometric Contraction (MVIC) value of the quadriceps muscle (dominant limb p = 0.001, non-dominant limb p < 0.001). There was no significant difference in the change of MVIC (ΔMVIC) of the quadriceps muscle between the Hybrid method and NMES groups on both sides of the leg.  Conclusion: Both Modified Hybrid Training (MHT) and the Neuro-Muscular Electrical Stimulation (NMES) are effective in increasing quadriceps muscle MVIC with comparable result.